Identification génétique et datation radiocarbone de restes osseux de cerf, de renne et de bison des steppes d’une sépulture moustérienne (La Ferrassie 8, Dordogne, France) - Elalouf, Jean-Marc; Utge, Jose; Lebon, Matthieu; Tombret, Olivier; Zazzo, Antoine; Balzeau, Antoine (Paléo, 2022)
To gain new information on the burial context of the La Ferrassie 8 Néandertal child, we studied uncharacterized bone remains originating from the locus where the partial human skeleton was found. We report here on the analysis of 20 bone splinters. Searching for mitochondrial DNA for 10 mammalian species, including Néandertal, we performed real-time PCR analyses and demonstrated the presence of red deer (Cervus elaphus), reindeer (Rangifer tarandus), or steppe bison (Bison priscus) DNA in three bone samples. Radiocarbon dating analysis of the samples that contained DNA yielded ages of about 55,000 to 42,000 years cal. BP. These values are in line with those previously obtained from a néandertal bone fragment and other animal remains from the same sector, whereas older ages have been reported for OSL-dated sediments from the same level. This study therefore supports the contention that the Néandertal child was laid in a pit dug into an archaeological sterile layer where faunal remains from upper layers fell when the pit was prepared or filled. Afin d’obtenir de nouvelles informations sur le contexte d’enfouissement de l’enfant néandertalien nommé La Ferrassie 8, nous avons analysé des restes indéterminés du locus où le squelette humain partiel a été découvert. Notre étude porte sur 20 esquilles osseuses où la présence d’ADN de 10 espèces, dont Néandertal, a été recherchée au moyen de tests spécifiques d’amplification génique (PCR en temps réel) de fragments du génome mitochondrial. Nous montrons la préservation de l’ADN dans trois esquilles, identifiées respectivement comme des restes de cerf élaphe (Cervus elaphus), de renne (Rangifer tarandus) et de bison des steppes (Bison priscus). La datation radiocarbone de ces esquilles donne des âges compris entre 55 000 et 42 000 ans cal. BP. Ceci les situe dans le même horizon chronologique que d’autres restes animaux et un reste néandertalien du même secteur, alors que les sédiments du même niveau datés par OSL apparaissent plus anciens. Nos données confortent la ...